2011
DOI: 10.4067/s0718-95162011000100004
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Bioavailability of Chlorpyrifos Residues in Soil to Earthworms

Abstract: An incubation test was conducted to investigate the effect of aging on bioavailability of chlorpyrifos in soil and to assess the feasibility of chemical extraction techniques for predicting bioavailability of chlorpyrifos in soil. Chlorpyrifos was spiked into sterilized soil and aged in microcosms for up to 120 days. The earthworms were incubated in the spiked soils, at 0, 7, 14, 30, 60, and 120 days after spiking, for a period of 7 days. After exposure, chlorpyrifos concentrations in the earthworm tissues wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 39 publications
1
14
0
1
Order By: Relevance
“…Ion H + contained in chemical fertilizer substitutes the inorganic pesticides molecul so the adsorption is decreased (Odukkathil and Vasudevan 2013). Continuous flooding desreases organophospate residue concentration because of leaching (Manuaba, 2009;Wu et al, 2011). Residue mobillity increasing due to irigation (Muller et al 2007) especially on the topsoil (Scholtz and Bidleman 2006) so the residue concentration decreased.…”
Section: Organophosphate Residue Concentration In Research Areamentioning
confidence: 99%
“…Ion H + contained in chemical fertilizer substitutes the inorganic pesticides molecul so the adsorption is decreased (Odukkathil and Vasudevan 2013). Continuous flooding desreases organophospate residue concentration because of leaching (Manuaba, 2009;Wu et al, 2011). Residue mobillity increasing due to irigation (Muller et al 2007) especially on the topsoil (Scholtz and Bidleman 2006) so the residue concentration decreased.…”
Section: Organophosphate Residue Concentration In Research Areamentioning
confidence: 99%
“…Currently, soil pollution by heavy metals is widespread (Calisi et al, 2013;Garg et al, 2009). The accumulation of heavy metals and organic pollutants (e.g., pesticides) in earthworms is speciesdependent (Garg et al, 2009;van Vliet et al, 2005;Wu et al, 2011). Garg et al (2009) reported that Cr and Pb concentrations were significantly higher in Allolobophora parva compared with Eisenia fetida, whereas accumulation of Zn was similar in both species.…”
Section: Introductionmentioning
confidence: 99%
“…A CaCl 2 solution is usually considered to be a "soft" extraction method for the labile fraction of chlorimuron-ethyl in soil (Barriuso et al, 2004); for example, it provided an indication of the amount of chlorimuron-ethyl that could be desorbed or that was water soluble and exchangeable. A mixture of aqueous solution and organic solvent, such as PBS-M, was expected to measure the fraction of chlorimuron-ethyl bound to soil organic matter (SOM) (Wu et al, 2011). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%